Pengaruh Latihan Tari Legong Terhadap Kebugaran Fisik Mahasiswi Semester VI dan VIII Fakultas Kedokteran Universitas Udayana - Riyanta, K. G. Budhi; N, Faradilla; **, Anggreini; Hindom, Maria C; Dwi Putra, A. A. D. Dalem; Weta, I Wayan (E-Jurnal Medika Udayana; vol 2 no4 (2013):e-jurnal medika udayana)
Sport is a way to promote health and prevent degenerative diseases. Sport has great benefits in improving physical fitness and maintaining ideal body weight. This study found that the potentials of domestic culture can be used as a form of sports. Legong dance is one of popular Balinese tradisional art which has dynamic movements with duration of 20 minutes. A randomized pre-test and post-test contol group design was carried out to compare the effectiveness of the Balinese Legong dance with Senam Ayo Bersatu (one of aerobic dance) in improving physical fitness and reducing body fat. Thirty samples who came from the sixth and eighth semester in the Faculty of Medicine Udayana University were divided into three different groups: I (Legong dance intervention), II (Senam Ayo Bersatu intervention), and control (without intervention). The intervention was done in 40 minutes for 8 weeks with three times intervention/week. Time of 2.4 km run as parameter of physical fitnees and body fat percentage was measured before starting the intervention and at last eighth weeks. It was elicited the significant difference (p?0.05) that Legong dance was more effective as Senam Ayo Bersatu in improving physical fitness and maintain body fat composition.
Keywords: Legong dance, sports, body fat percentage, physical fitness.